﻿Prevalence and eradication efficacy of Helicobacter pylori infection in children in the Mekong delta, Vietnam: a cross-sectional study - Duc Long Tran; Trung Kien Nguyen; Thi Thu Cuc Nguyen; Thi Thuy Loan Le; Cong Ly Tran; Thi Gai Le; Duy Toan Pham; Minh Phuong Nguyen (Pharmacia, 2022)
Background: Worldwide, Helicobacter pylori (HP) infection in children with peptic ulcer and/or gastritis (PUG) is increasingly common. In Vietnam, clinical symptoms of HP infection in PUG children are often non-specific, and treatment regimens currently have a low success rate. Objective: This study determined the HP infection prevalence, its clinical and endoscopic findings, and its associated factors. Additionally, the efficiencies of HP treatment regimens in PUG children were also evaluated. Design and setting: A cross-sectional descriptive study was conducted on 140 pediatric patients diagnosed with PUG at Can Tho Children’s Hospital from 2017–2019. Results: The prevalence of HP infection in PUG children was 46.4%. A significant association was found between HP infection and patient possessing a family history of HP infection (aOR: 2.35 (1.1–4.76). Symptoms of abdominal pain accounted for the highest rate of 88.6%, followed by vomiting, heartburn, epigastric burning, and gastric bleeding (57.9%, 36.4%, 22.9%, and 13.6%, respectively). Endoscopic findings denoted that inflammatory lesions accounted for 85% and ulcers accounted for 15%. The successful HP eradication rate using the PAM regimen (Proton pump inhibitor/amoxicillin/metronidazole) was 51.8%, with 13.6% of PUG children encountering side effects. Conclusion: PUG children have a high rate of HP infection. Clinical symptoms are often non-specific, in which abdominal pain is the most common symptom. The success of HP eradication by the standard guideline of the Vietnam Ministry of Health is quite low. Thus, critical adjustments in the regimens are necessary.